2011
DOI: 10.1007/s00044-011-9605-5
|View full text |Cite|
|
Sign up to set email alerts
|

Antibacterial and antifungal activities of some trimethoprim salts

Abstract: In this study, the antimicrobial activities of Trimethoprim (1), Trimethoprim ? Maleic acid (2), Trimethoprim ? Oxalic acid dihydrate (3), and Trimethoprim ? trans-1,2-Cyclohexanedicarboxylic acid (4) were investigated for their in vitro growth inhibitory activity against human pathogenic as some bacteria and fungi. Substances were tested using the micro-broth dilution assay. The chemical agents showed the same activity against Escherichia coli, Pseudomonas aeruginosa, and Proteus vulgaris. Inhibitory activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar to SMX the therapeutic efficacy of drug can be maximized by combining TMP with some organic or inorganic salts in terms of increasing solubility and plasma half life of the drug in the body. Following this trend, some recent papers reported that combination of TMP with organic/inorganic salts can significantly improve drug performance (Tunalı et al 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to SMX the therapeutic efficacy of drug can be maximized by combining TMP with some organic or inorganic salts in terms of increasing solubility and plasma half life of the drug in the body. Following this trend, some recent papers reported that combination of TMP with organic/inorganic salts can significantly improve drug performance (Tunalı et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Alternatively, TMP may be incorporated with any organic acid such as lactic acid, citric acid, tartaric acid, maleic acid, malic acid, glutamic acid and aspartic acid in order to promote absorption, the rate of absorption and to facilitate biocompatibility of TMP. According to a literature example, sulfate, citrate, lactate, tartrate, malate and maleate compounds were coupled with TMP (Tunalı et al 2011) and the conjugates were found to be more potent than the drug used alone. In this case, Tunalı et al showed the antibacterial and antifungal activities of these TMP conjugates but the effects of these compounds on mammalian cells have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…APAP is an antipyretic pain killer that has been observed to have antimicrobial properties at concentrations above therapeutic use (Zimmermann and Curtis, 2017), and observed to have growth promoting effects on microorganism at therapeutic concentrations (Carvalho et al, 2010). TMP and SMX are antibiotics that are commonly taken in combination, but exhibit antimicrobial effects independently (Reeves and Wilkinson, 1979;Hida et al, 2005;Tunali et al, 2012). GEM is a medication used to treat high blood pressure, but has been observed to increase the antimicrobial potency of some pharmaceuticals (Rudin et al, 1992;Bulatova and Darwish, 2008) and to have direct impacts on plant growth (D'Abrosca et al, 2008;Pino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%